Iris Anti-Spoofing Using Image Quality Measures - Habib, Hussaini (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Spoof detection is a critical issue for the recognition of iris because it reduces the risk of forging iris recognition systems. The most relevant iris spoofing attacks reported in previous studies follows one of the three trends: photo attacks, contact-lens attacks or artificial-eye attacks. Spoofing attacks have prompted the biometric research community to learn more about the threat posed by these kinds of attacks on iris, fingerprint and face biometric systems. In this thesis, various Image Quality Assessment techniques to detect fake and real iris images presented to biometric systems were used. In this context, full reference image quality assessment measures such as Error Sensitivity Measures, Structural Similarity Measures and Information Theoretic Measures are implemented to distinguish fake and real iris images. Full-reference Image Quality Measures are also concatenated using feature-level fusion strategy. We propose to fuse twenty one full-reference image quality measures for iris anti-spoofing against print-attacks, contact-lens attacks and artificial-eye attacks. In order to evaluate the performance of the proposed iris anti-spoofing method using feature-level fusion of Image Quality Assessment techniques, two publicly available databases, namely CASIA and IIITD, were used. A comparative analysis of the performance of these Image Quality Assessment metrics is performed towards the completion of the thesis on various iris spoofing datasets of the aforementioned iris spoofing databases.

ÖZ: İris tanıma sistemlerinde, saldırı tespiti kritik bir konudur, çünkü bu işlem sistemin güvenilirliğini kaybetme riskini azaltır. Literatürde bahsedilen en belirgin iris yanıltma saldırısı; fotoğraf saldırısı, kontak lens saldırısı ve yapay göz saldırısı olarak üç çeşit olarak belirlenmiştir. İris, paramakizi ve yüz biyometri sistemlerine yapılan yanıltma saldırıları, biyometri alanında çalışma yapan araştırmacıları bu yöndeki tehditler üzerinde çalışmaya yöneltmiştir. Bu tezde, biyometrik sistemler için kullanılan gerçek ve sahte iris görüntülerinin tespiti için birçok Görüntü Kalitesi Değerlendirme tekniği kullanılmıştır. Bu bağlamda, Hata Hassasiyeti Ölçümü, Yapısal Benzerlik Ölçümü, Kuramsal Bilgi Ölçümü gibi kaynağa bağlı Görüntü Kalitesi Değerlendirme teknikleri, sahte ve gerçek iris görüntülerinin ayırt edilmesi için uygulanmıştır. Görüntü Kalitesi Değerlendirme teknikleri ayrıca öznitelik-seviyesi kaynaşımı ile birleştirilerek yeni bir yöntem önerilmiştir. Önerilen yöntemde, yirmi bir Görüntü Kalitesi Değerlendirme tekniği birleştirilip, yazdırma saldırısı, kontak lens saldırısı ve yapay göz saldırısına karşı yanıltma karşıtı bir yöntem geliştirilmiştir. Öznitelik-seviyesi kaynaşımı kullanarak Görüntü Kalitesi Değerlendirme teknilerini birleştiren önerilen iris yanıltma karşıtı yöntemin performansı, CASIA ve IIITD iris veritabanları kullanılarak yapılmıştır. Görüntü Kalitesi Değerlendirme tekniklerinin karşılaştırmalı performans analizi, belirtilen iris veritabanlarının çeşitli veri kümeleri üzerinde yapılmış ve tezin sonunda sunulmuştur.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2019. Supervisor: Assoc. Prof. Dr. Önsen Toygar.
Keywords: Computer Pattern Recognition; Image processing--Pattern recognition systems; Spoof Detection; Iris recognition; Photo Attack; Contact Lens Attack; Image Quality Assessment; Computer Engineering